Carnitine deficiency among hospitalized pediatric patients: A retrospective study of critically ill patients receiving extracorporeal membrane oxygenation therapy. Issue 8 (7th October 2021) - Kelley, Jenna; Sullivan, Erin; Norris, Marie; Sullivan, Sarah; Parietti, Jennifer; Kellogg, Kimberly; Scott, Anna I.
Abstract: Background: The metabolic demands associated with critical illness place patients at risk for nutrition deficits. Carnitine is a small molecule essential for fatty acid oxidation and gluconeogenesis. Secondary carnitine deficiency can have clinically significant complications and has been observed anecdotally in patients receiving extracorporeal membrane oxygenation (ECMO) therapy at our institution. Guidelines for monitoring and supplementing carnitine are lacking. This retrospective study determined whether critically ill pediatric patients receiving ECMO have an increased risk of carnitine deficiency. Methods: Acylcarnitine analysis was performed on residual specimens from patients who received ECMO therapy. The control data were a convenience sample gathered by chart review of patients who had been tested for carnitine during a hospitalization. Results: Acylcarnitines were measured in 217 non‐ECMO patients and 81 ECMO patients. Carnitine deficiency, based on age‐specific reference ranges, was observed in 41% of ECMO cases compared with 21% of non‐ECMO cases. Multivariable analysis of age‐matched patients identified that the odds of carnitine deficiency were significantly lower among patients on the floor compared with ECMO patients (odds ratio, 0.21; 95% CI, 0.10–0.44). Age‐specific frequency of qualitative carnitine deficiency ranged from 15% (patients >5 years old) to 56% (patients 1 week to 1 month old) in ECMO patients and 15% (patients >5 years old) to 34% (patients 1–5 years old) in non‐ECMO patients. Conclusion: In this study, ECMO patients were carnitine deficient more frequently compared with other inpatients, with the highest rates of deficiency among ECMO patients between 1 week and 1 month old.